Lying and deception theory and practice - Carson, Thomas L., 1950- (Oxford : Oxford University Press, 2010)
This is a comprehensive and up-to-date investigation of moral and conceptual questions about lying and deception. Carson argues that there is a moral presumption against lying and deception that causes harm, he examines case-studies from business, politics, and history.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Truthfulness and falsehood; Truthfulness and falsehood -- Case studies